East Asian buntings: Ongoing illegal trade and encouraging conservation responses. Issue 6 (23rd March 2021) - Heim, Wieland; Chan, Simba; Hölzel, Norbert; Ktitorov, Pavel; Mischenko, Alexander; Kamp, Johannes
Abstract: The dramatic decline in the once superabundant Yellow‐breasted Bunting Emberiza aureola, a widely distributed Eurasian songbird, triggered worldwide media interest. Five years after the initial publication, we set out to give an update on the status of this critically endangered species, the conservation actions that followed, and the lessons that can be learned from this exceptional case for the conservation of migratory land birds in Asia and beyond. While there are signs of possible population recovery in the Yellow‐breasted Bunting, other migratory songbird species were recently observed to be trapped in huge numbers, which could lead to further declines. We argue that the Yellow‐breasted Bunting can be used as a flagship species to promote the conservation of East Asian land bird migrants.